2021
DOI: 10.1007/s00345-021-03653-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of patients’ sex with treatment outcomes after intravesical bacillus Calmette–Guérin immunotherapy for T1G3/HG bladder cancer

Abstract: Purpose To investigate the association of patients’ sex with recurrence and disease progression in patients treated with intravesical bacillus Calmette–Guérin (BCG) for T1G3/HG urinary bladder cancer (UBC). Materials and methods We analyzed the data of 2635 patients treated with adjuvant intravesical BCG for T1 UBC between 1984 and 2019. We accounted for missing data using multiple imputations and adjusted for covariate imbalance between males and females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Meta-analysis of 31 studies by Mori et al revealed that there is no gender-specific difference in the overall survival, recurrence-free survival, and progression-free survival in NMIBC patients after surgical removal of tumor and BCG treatment [ 51 , 52 ]. However, the meta-analysis of 63 studies of MIBC patients showed a gender-specific difference in overall survival, recurrence-free survival, and progression-free survival [ 51 ].…”
Section: Clinical Aspects Of Sex and Gender Differences In Bladder Ca...mentioning
confidence: 99%
“…Meta-analysis of 31 studies by Mori et al revealed that there is no gender-specific difference in the overall survival, recurrence-free survival, and progression-free survival in NMIBC patients after surgical removal of tumor and BCG treatment [ 51 , 52 ]. However, the meta-analysis of 63 studies of MIBC patients showed a gender-specific difference in overall survival, recurrence-free survival, and progression-free survival [ 51 ].…”
Section: Clinical Aspects Of Sex and Gender Differences In Bladder Ca...mentioning
confidence: 99%
“…Similarly, Palou et al [9], in their single-center retrospective series of 146 primary T1G3 patients, reported an independent association between female sex and RFS, PFS, and CSS. More recently, D’Andrea et al [10] analyzed the data of 2635 T1 patients treated with BCG; after adjusting for differences in baseline patients’ and tumor's characteristics, female sex was associated with disease progression (HR 1.25) but not with recurrence. However, this association was no longer present when the analysis was restricted to patients treated with adequate BCG therapy.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…However, the standard HRBC management involves thorough transurethral resection of the bladder tumor (TURBT) supplemented with a second restaging TUR (reTUR) and adjuvant intravesical instillations of Bacillus Calmette–Guérin (BCG). Given this complexity of HRBC management, the evidence concerning disparate outcomes between males and females remains inconclusive [ 8 ]. The aim of the study is to determine sex diversities in the treatment and oncologic outcomes of primary non-muscle-invasive high-risk bladder cancer in comprehensive, high-volume centers.…”
Section: Introductionmentioning
confidence: 99%